Who is Resilient in a Time of Crisis? The Importance of Financial and Non-Financial Resources - David W. Johnston; Claryn S. J. Kung; Michael A. Shields (Institute of Labor Economics (IZA), 2020)
We identify the individual resources that predicted psychological resilience during the COVID-19 lockdown. Using UK data, we compare psychological distress observed before COVID-19 with distress measured in April, May, and June 2020. After matching respondents on key characteristics, we find that the most important predictor of resilience is non-cognitive skills, as measured by self-efficacy. Self-efficacy also reduces the psychological effects of negative earnings shocks. Neither income, wealth, cognitive ability, nor social capital predicted resilience. Our findings hold when comparing differences between household members. These findings support investments in non-cognitive skill development in order to reduce the damage-function from adverse events.
Keywords: I10; C2; C5; 330; resilience; psychological health; resources; non-cognitive; COVID-19; panel